Chronic kidney disease and oral health – a review - Kuba Sękowski; Justyna Grudziąż-Sękowska; Agnieszka Osiadło; Ryszard Gelert; Jarosław Pinkas; Janusz Ostrowski (Wiedza Medyczna, 2025)
Chronic kidney disease (CKD) and oral diseases are interrelated, especially in hemodialysis patients who are more susceptible to infections, periodontal diseases, and other dental issues. The increased risk of these conditions is due to metabolic disturbances, dry mouth, immune dysfunction, and side effects of treatment. Periodontal disease negatively impacts CKD management and increases cardiovascular risk. Therefore, the inclusion of prevention, diagnosis, and treatment of oral diseases in the treatment plan for CKD patients is essential to improving quality of life and treatment outcomes.